Maternal Mortality in a District Hospital of Bangladesh An In-Depth Search of the Underlying Causes - Ashraf, Fatema; Mustanzid, SM; Khanom, Marina (TAJ: Journal of Teachers Association, 2009)
Maternal death is a tragedy - a social injustice to individual women, to a family and to their community. To reduce maternal mortality is at the top of the national health priorities. Emergency obstetric care service is thought to be the basis of reducing maternal mortality and morbidity. This study was carried out to determine the case fatality rate and risk factors of maternal mortality in Kushtia General Hospital, a secondary health care facility, where comprehensive Emergency Obstetric Care (EmOC) service is established. A total of 3,709 cases were admitted with pregnancy or related complications during pregnancy or within 42 days of confinement, from August 1999 to July 2000. Among them 3,186 were obstetric patients and 523 were gynaecological cases. Within this 12-months period 37 mothers died. Clinical causes of deaths were: 32 (86.48%) due to eclampsia, 3 (8.1%) due to ruptured uterus with shock, 1 (2.7%) due to induced incomplete abortion with shock and 1 (2.7%) due to PPH with shock. Almost 100% of the deaths could be prevented if they had come to the hospital at an earlier part of the disease. Responsible factors for these deaths could be at personal, familial, socio-cultural or health care center level. So this study was carried out to identify the risk factors of maternal death and also the status of health care delivery system at the peripheral level of the country i.e. the EmOC delay model in this perspective has been tried to identify. doi: 10.3329/taj.v20i2.3068 TAJ 2007; 20(2): 99-106